Case Report: Contiguous presentation of anti-MDA5 juvenile dermatomyositis and anti-AQP4 neuromyelitis optica spectrum disorder in an adolescent patient - Wiersma, Rebecca E.; Shaheen, Zachary R.; Correll, Colleen K.; Hobday, Patricia M. (Frontiers in Pediatrics, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare inflammatory central nervous system (CNS) disorder that is known to be associated with other neurologic and organ-specific autoimmune conditions. There has been increasing recognition of the association between NMOSD and systemic autoimmune disease, most commonly systemic lupus erythematosus (SLE) and Sjogren's Syndrome (SS). We report a case of an adolescent presenting with anti-melanoma differentiationassociated protein 5 juvenile dermatomyositis (anti-MDA5 JDM) and NMOSD, with clinical features of myelitis, polyarthritis, myositis, and skin involvement. Currently there are only two other published cases describing NMOSD associated with anti-MDA5 dermatomyositis, both in adults; to our knowledge, this is the first case in an adolescent patient.